Brain to brain musical interaction: A systematic review of neural synchrony in musical activities - Cheng, Shate; Wang, Jiayi; Luo, Ruiyi; Hao, Ning (Neuroscience and biobehavioral reviews, 2024)
The use of hyperscanning technology has revealed the neural mechanisms underlying multi-person interaction in musical activities. However, there is currently a lack of integration among various research findings. This systematic review aims to provide a comprehensive understanding of the social dynamics and brain synchronization in music activities through the analysis of 32 studies. The findings illustrate a strong correlation between inter-brain synchronization (IBS) and various musical activities, with the frontal, central, parietal, and temporal lobes as the primary regions involved. The application of hyperscanning not only advances theoretical research but also holds practical significance in enhancing the effectiveness of music-based interventions in therapy and education. The review also utilizes Predictive Coding Models (PCM) to provide a new perspective for interpreting neural synchronization in music activities. To address the limitations of current research, future studies could integrate multimodal data, adopt novel technologies, use non-invasive techniques, and explore additional research directions. •The first systematic review of multi-person music activities using hyperscanning technology.•It provides a novel perspective for interpreting neural synchronization in music activities.•The neural synchronization and collaborative behavior in music activities are not simply positively correlated.